Plain Text Encryption Using AES, DES and SALSA20 by Java Based Bouncy Castle API on Windows and Linux - Panda, Madhumita; Nag, Atul (2015 Second International Conference on Advances in Computing and Communication Engineering, 2015)
Information Security has become an important element of data communication. Various encryption algorithms have been proposed and implemented as a solution and play an important role in information security system. But on the other hand these algorithms consume a significant amount of computing resources such as CPU time, memory and battery power. However, for all practical applications, performance and the cost of implementation are also important concerns. Therefore it is essential to assess the performance of encryption algorithms. In this paper, the performance of three Symmetric Key based algorithms-AES, Blowfish and Salsa20 has been evaluated based on execution time, memory required for implementation and throughput across two different operating systems. Based on the simulation results, it can be concluded that AES and Salsa20 are preferred over Blowfish for plain text data encryption.